Novel Polymorph of Favipiravir—An Antiviral Medication - Alexander S. Goloveshkin; Alexander A. Korlyukov; Anna V. Vologzhanina (Pharmaceutics, 2021)
Various solid forms of pharmaceutically important compounds exhibit different physical properties and bioactivity; thus, knowledge of the structural landscape and prediction of spontaneous polymorph transformations for an active pharmaceutical ingredient is of practical value for the pharmaceutical industry. By recrystallization from ethyl acetate, a novel polymorph of 6-fluoro-3-hydroxypyrazine-2-carboxamide (trademark favipiravir, RNA polymerase inhibitor) was obtained and characterized using differential scanning calorimetry (DSC), infra-red spectroscopy and powder X-ray diffraction (XRD) analysis. The favipiravir molecule in two polymorphs realizes similar H-bonding motifs, but the overall H-bonded networks differ. Based on periodic density functional theory calculations, the novel tetragonal polymorph with two interpenetrated H-bonded networks is slightly less stable than the orthorhombic one with the zst topology of the underlying H-bonded net that is in accord with experimentally observed powder XRD patterns of slow conversion of the tetragonal phase to the orthorhombic one. However, topological analysis of net relations revealed that no transformations can be applied to convert H-bonded networks in the experimental unit cells, and DSC data indicate no solid-state reactions at heating.